Struktur Sistem Informasi Manajemen (SIM) dalam Lembaga Pendidikan di MTs EXPGA (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the structure of the Management Information System (MIS) implemented in MTs EXPGA as a secondary educational institution. MIS is an important instrument in supporting decision making, managing academic and non-academic data, and improving the efficiency of school administration. This research method uses a qualitative descriptive approach with observation, interview, and documentation techniques. The results of the study indicate that the MIS structure in MTs EXPGA is divided based on operational, managerial, strategic, and decision support functions. Although the implementation of this system has covered the basic needs of school management, improvements are still needed in terms of data integration and HR training. This article provides recommendations for improvements to optimize the use of MIS in supporting educational goals in the digital era.